Gambaran Asupan Protein dan Seng (Zn) dengan Kejadian Stunting pada Anak Baduta - March Dilla Arianggi Rambe; Ginta Siahaan (NUTRIENT, 2021)
This study aims to determine the description of protein and zinc (zn) intake with the incidence of stunting in children under two years old in the working area of the Mandala Health Center Medan. This research method is descriptive with a cross sectional design. The results of this study from a total of 45 samples of children under the age of five in the working area of the Mandala Health Center Medan with stunting, it was found that 71% of children under two years were not stunted and who were stunted were 29% with protein intake (46.67%) and zinc intake (42.2%) included in the category good. In conclusion, the better the intake of protein and zinc (Zn), the incidence of stunting will be very small.   Keywords: Baduta Children, Protein, Zinc (Zn), Stunting